2017
DOI: 10.1055/s-0043-102492
|View full text |Cite
|
Sign up to set email alerts
|

Safety of ERCP in patients with liver cirrhosis: a national database study

Abstract: Background and aims Given the limited data on the safety of endoscopic retrograde cholangiopancreatography (ERCP) in patients with liver cirrhosis, we attempted to evaluate this question using a large national database. Methods We conducted a matched case – control study using the 2010 National Inpatient Sample database in which four non-cirrhotic controls were matched randomly for every cirrhotic patient from the same 10-year age group. We compared adverse events and safety of inpatient ERCP between patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
62
2
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(68 citation statements)
references
References 18 publications
2
62
2
2
Order By: Relevance
“…A large case‐controlled study reported higher risk of bleeding after ERCP in patients with liver cirrhosis (2.1% vs 1.2%) . A retrospective study in China with 46 liver cirrhotic patients who underwent ERCP reported that ERCP was relatively safe for cirrhotic patients with Child‐Pugh A and B, while those with Child‐Pugh C had an increased risk of bleeding .…”
Section: Medical Prevention Of Post‐ercp Complicationsmentioning
confidence: 87%
See 1 more Smart Citation
“…A large case‐controlled study reported higher risk of bleeding after ERCP in patients with liver cirrhosis (2.1% vs 1.2%) . A retrospective study in China with 46 liver cirrhotic patients who underwent ERCP reported that ERCP was relatively safe for cirrhotic patients with Child‐Pugh A and B, while those with Child‐Pugh C had an increased risk of bleeding .…”
Section: Medical Prevention Of Post‐ercp Complicationsmentioning
confidence: 87%
“…A large case-controlled study reported higher risk of bleeding after ERCP in patients with liver cirrhosis (2.1% vs 1.2%). 95 A retrospective study in China with 46 liver cirrhotic patients who underwent ERCP reported that ERCP was relatively safe for cirrhotic patients with Child-Pugh A and B, while those with Child-Pugh C had an increased risk of bleeding. 96 In another retrospective study of ERCP-related complications in 121 patients who underwent liver transplantation, the incidences of PEP, biliary infection, and postoperative bleeding were 3.7%, 3.3%, and 1.6%, respectively, which was comparable to those of post-ERCP complications in non-liver transplant patients.…”
Section: Patients With Cirrhosis and Liver Transplantationmentioning
confidence: 99%
“…Liver cirrhosis is reportedly one of the risk factors that are associated with a low success rate and a high rate of adverse events. Previous studies have reported that decompensated liver cirrhosis is a risk factor for post‐ERCP hemorrhage and pancreatitis (PEP) . Although these results are intuitively reliable, it is necessary to consider whether the definition of decompensation are appropriate or not.…”
Section: Introductionmentioning
confidence: 99%
“…Other than the study by Navaneethan et al ., most of these authors used the Child–Turcotte–Pugh classification in defining liver decompensation. However, this score may be biased by the patient's status before ERCP; moreover, the Child–Turcotte–Pugh classification score is a prognostic index rather than an indicator of liver dysfunction itself .…”
Section: Introductionmentioning
confidence: 99%
“…An increased risk of pancreatitis has also been shown to be associated with younger age and the presence of hypertriglyceridaemia, and a reduced risk associated with the use of insulin and long‐term use of metformin in diabetic patients. Finally, patients with more advanced cirrhosis (Child–Pugh grade B and C) have a higher incidence of ERCP complications than those with Child–Pugh grade A, and an increased risk of postprocedure bleeding, although not of PEP.…”
Section: Introductionmentioning
confidence: 99%